Development of an Integrated Electronics Learning Module Using Sensors and Arduino to Enhance Conceptual Understanding in Physics - Riskawati; Rusdiana, Dadi; Abdurrahman; Said, Sukmawati; Sanusi, Dirgah Kaso; Indira, Ihfa (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Microcontroller-based learning is increasingly used in physics education; however, evidence of its impact on students’ conceptual understanding remains inconsistent. This study evaluated a project-based, sensor-integrated Arduino learning module designed to enhance students’ conceptual understanding in an undergraduate physics/electronics course. Using a one-group pretest–posttest design, the module was implemented with 59 students and developed through the 4D model. The learning activities were organized into iterative project cycles, including system design, programming, sensor calibration, data collection, and reflection. Data were collected through expert validation sheets, a conceptual understanding test administered before and after the intervention, and a student response questionnaire. The data were analyzed using feasibility ratings, normalized gain (g), a paired-samples t test, and Cohen’s d. Expert reviewers rated the module as highly feasible and very valid. Students’ conceptual understanding improved significantly, as indicated by a moderate normalized gain (g = 0.48) and a large effect size (d = 1.01). In addition, students reported high engagement and perceived the module as practical for learning. Although these findings are encouraging, the use of a single-group design and implementation at a single site limit causal inference and generalizability. Future studies are therefore recommended to employ comparative and multi-site research designs.